Closing-in Behavior and Parietal Lobe Deficits: Three Single Cases Exhibiting Different Manifestations of the Same Behavior - Ambron, Elisabetta; Piretti, Luca; Lunardelli, Alberta; Coslett, H. Branch (Frontiers in Psychology, 2018)
Closing-in behavior (CIB) is observed in copying tasks (graphic or gestural) when the copy is performed near or on the top of the model. This symptom has been classically considered to be a manifestation of constructional apraxia and is often associated with a visuospatial impairment. More recent work emphasizes the attentional and/or executive nature of the behavior and its association with frontal lobe dysfunction. We describe three individuals in whom CIB was associated with posterior parietal alterations of different etiologies (stroke in Subject 1 and dementia in Subject 2 and 3). In copying figures, Subject 1 produced the shape with high accuracy but overlapped the model, while for Subjects 2 and 3 the were distorted but overlapping or in close proximity to the target. In gesture imitation, Subject 2 performed the gestures towards the examiner’s space, while Subject 1 showed a peculiar form of CIB: when he was asked to place the ipsilesional arm in a position that mirrored the contralesional hand Subject 1 moved his hand and touched his contralesional hand. Whereas CIB in Subject 1 was associated with selective deficits in executive functions and attention, additional visuospatial deficits were observed in Subject 2 and 3. These patients showed a general visuo-constructional deficit, involving constructional, limb and dressing. These case studies support a primary attentional account of CIB but also suggest that visuo-constructional impairments may contribute to the emergencey of CIB, in some. Furthermore, they support the hypothesis of a fronto-parietal network involvement in the anatomical basis of CIB.